2019
DOI: 10.1182/blood-2019-123156
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Second Primary Malignancies and Peripheral Sensory Neuropathy in Patients with Multiple Myeloma Receiving Daratumumab Containing Regimen

Abstract: Introduction: Proteasome inhibitors-based regimens are the mainstay of initial therapy for most patients with multiple myeloma. Daratumumab is a human IgGκ monoclonal antibody that targets CD38 with direct antitumor effects and has an immunomodulatory component. Recent studies have demonstrated that addition of daratumumab to standard regimens enhance direct cytotoxicity on myeloma cells and have shown survival benefits. Yet, there are notable safety concerns. We performed a combined analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Besides the bone marrow, other tissues, like peripheral and central neurons, also express CD38 which could raise clinical concern 37 . A previous meta-analysis demonstrated that the risk for peripheral neuropathy does not increase with the addition of daratumumab 36 . This study covered the literature until June 2019.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Besides the bone marrow, other tissues, like peripheral and central neurons, also express CD38 which could raise clinical concern 37 . A previous meta-analysis demonstrated that the risk for peripheral neuropathy does not increase with the addition of daratumumab 36 . This study covered the literature until June 2019.…”
Section: Discussionmentioning
confidence: 96%
“…Despite the enhanced cytotoxicity on myeloma cells, better survival results, and therapeutic response, safety concerns arise 36 as the target of this antibody is expressed on haematopoietic cells 37 . In NDMM, both all grade and grade 3–4 lymphopenia (moderate certainty) and neutropenia (low certainty) were more likely to appear in patients on daratumumab.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation